IMPACTS OF DIFFERENT SOCIAL SYSTEMS ON INCOME SITUATION OF HOUSEHOLDS - NaÄa, BirÄiakovÃ¡; Jana, StÃ¡vkovÃ¡; Veronika, AntoÅ¡ovÃ¡ (European Scientific Journal, ESJ, 2014)
Social policy affects the life of every individual in society. Its main aim is to eliminate social inequality. Success in fulfilling such a goal is influenced by the applied social system. Income inequality is the most frequently used expression of social inequality. Authors of the presented paper describe analysis of income and expenditure of households collated in variousquintiles, taking into account the effect of social transfers on the total amount of income. Respecting fundamental social systems and monitoring their effectiveness, as the topic of interest income data from the Czech Republic, UK, Sweden and Germany was chosen. The data was taken from Eurostat, in the period of 2003-2013. Conclusions are compared with results of the income poverty analysis as the income poverty is the most common form of poverty in the EU countries.